2010
DOI: 10.1158/0008-5472.can-10-0545
|View full text |Cite
|
Sign up to set email alerts
|

FoxM1 Mediates Resistance to Herceptin and Paclitaxel

Abstract: Inherent and acquired therapeutic resistance in breast cancer remains a major clinical challenge. In human breast cancer samples, overexpression of the oncogenic transcription factor FoxM1 has been suggested to be a marker of poor prognosis. In this study, we report that FoxM1 overexpression confers resistance to the human epidermal growth factor receptor 2 monoclonal antibody Herceptin and microtubule-stabilizing drug paclitaxel, both as single agents and in combination. FoxM1 altered microtubule dynamics to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
166
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 41 publications
8
166
0
Order By: Relevance
“…FOXM1 has only recently been implicated in the response to DNA damage in pancreatic and breast cancer cell lines (21). On top of that, FOXM1 has been shown to mediate resistance to different drugs, such as herceptin, paclitaxel, cisplatin, and epirubicin (25)(26)(27)(28). We showed that FOXM1 knockdown also leads to radiosensitization in NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 74%
“…FOXM1 has only recently been implicated in the response to DNA damage in pancreatic and breast cancer cell lines (21). On top of that, FOXM1 has been shown to mediate resistance to different drugs, such as herceptin, paclitaxel, cisplatin, and epirubicin (25)(26)(27)(28). We showed that FOXM1 knockdown also leads to radiosensitization in NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 74%
“…20 It has been demonstrated that overexpression of FoxM1 specifically protects against apoptotic cell death FoxM1 is a valid strategy for developing novel anticancer drugs, overexpression of FoxM1 exhibits resistance to anticancer drugs. Bortezomib (Velcade) was the first PI approved for the treatment of human cancer (multiple myeloma) in 2003, with probable benefits against other types of cancer.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Recent studies have reported that aberrant expression of FOXM1 in a variety of human cancers is associated with their aggressive behavior. 19,20 While targeting Figure 1. Pis sensitized the human cancer cells to apoptotic cell death following knockdown of FoxM1.…”
mentioning
confidence: 99%
“…It is important to note that attenuating the activity of FoxM1 in traztuzumabresistant breast cancer cells has also been shown to increase their sensitivity to traztuzumab, a tyrosine kinase receptor antibody inhibitor that targets the HER2 oncogene product. Traztuzumab, in fact, shares similar signaling pathway inhibition with gefitinib, including PI3K/Akt [26] . Moreover, the knockdown of FoxM1 expression can induce apoptosis in breast cancer cells that are otherwise resistant to cisplatin [25] .…”
Section: Discussionmentioning
confidence: 98%
“…FoxM1, a member of the Forkhead box family of transcription factors, is known to play an important role in cell cycle progression [23,24] and is overexpressed in a panel of solid tumors, including liver, lung, cervical, colorectal and breast cancers [7,[9][10][11] . FoxM1 also participates in the drug resistance of various cancer cells by protecting cancer cell proliferation and abrogating apoptosis [25,26] . For example, enhanced expression of FoxM1 was reported to inhibit cell death induced by gefitinib in some breast cancer cell lines [15] .…”
Section: Discussionmentioning
confidence: 99%